Yes, correct context is indeed the key: An answer to Haave‐Audet et al. 2019. (3rd November 2019) - Herczeg, Gábor; Urszán, Tamás János; Orf, Stephanie; Nagy, Gergely; Kotrschal, Alexander; Kolm, Niclas
Abstract: We published a study recently testing the link between brain size and behavioural plasticity using brain size selected guppy ( Poecilia reticulata ) lines (2019, Journal of Evolutionary Biology, 32, 218‐226). Only large‐brained fish showed habituation to a new, but actually harmless environment perceived as risky, by increasing movement activity over the 20‐day observation period. We concluded that "Our results suggest that brain size likely explains some of the variation in behavioural plasticity found at the intraspecific level". In a commentary published in the same journal, Haave‐Audet et al. challenged the main message of our study, stating that (a) relative brain size is not a suitable proxy for cognitive ability and (b) habituation measured by us is likely not adaptive and costly. In our response, we first show that a decade's work has proven repeatedly that relative brain size is indeed positively linked to cognitive performance in our model system. Second, we discuss how switching from stressed to unstressed behaviour in stressful situations without real risk is likely adaptive. Finally, we point out that the main cost of behavioural plasticity in our case is the development and maintenance of the neural system needed for information processing, and not the expression of plasticity. We hope that our discussion with Haave‐Audet et al. helps clarifying some central issues in this emerging research field. Abstract : We tested the link between relative brain size and behavioural plasticity recently (Herczeg et al. 2019, Journal of Evolutionary Biology, 32, 218‐226). In their commentary, Haave‐Audet et al. stated that (i) relative brain size is not a suitable proxy for cognitive ability and (ii) habituation measured by us is likely not adaptive and costly. Here, we show that a positive link between relative brain size and cognitive performance has been repeatedly proven in our system. Then, we argue that habituation in the absence of risk is likely adaptive. Finally, we point out that the costs of capacity, and not the costs of expression, are important for behavioural plasticity in our laboratory experiment.